(untitled) (Research, Society and Development, 2020)
Objective: to analyze the medical call center performed in a school clinic in Teresina-PI during quarantine. Methodology: studycross-sectional and retrospective, based on teleconsultations carried out between May 18 and July 18, 2020 at the teaching hospital of Centro Universitário UNINOVAFAPI. The collection of information was done through reports issued, through administration, of the medical records system. Variables analyzed: attendance; sex; age; marital status; municipality of residence and specialty. Results: 171 visits were made, 121 of whom were female and 50 were male. Of the total, 37% were over 60 years old and 45% were married. Teresina had a greater number of patients seen and, of the specialties offered, endocrinology represented the highest percentage of consultations. Conclusion: The analysis corroborated the increase in the practice of telemedicine during the pandemic, allowing health care to the population. However, some disadvantages must be taken into account for the evolution of this type of service and to make it more universal.